Obligation and Sovereign Virtue in Hobbes's Leviathan. Issue 1 (9th January 2017) - Hoye, J. Matthew
Abstract: Debates regarding obligation in Hobbes have turned on either natural right or natural law interpretations. Both interpretations tend to take up the question of obligation from the perspective of teaching those who contend "for too great Liberty" "how to obey." But Hobbes also has a second audience, and a second goal in mind: those who contend "for too much Authority" must be taught "how to govern." From that perspective, a different discussion of obligation emerges. What is revealed is a contiguous set of reflections in Leviathan that pivot on the character of the sovereign and the citizens' judgment thereof, all of which inform effective obligation and have little in common with received interpretations of obligation. It further reveals a relationship between the failure to manifest sovereign virtue and the natural punishment of pusillanimous and barbaric sovereigns. That is, it speaks to a sovereign virtue ethic in Leviathan .